Physarum nudum T. Macbr. — новий для України вид міксоміцетів - Дудка, І.О.; Леонтьєв, Д.В.; Бондаренко-Борисова, І.В. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Сообщается о находке Physarum nudum T. Macbr. — нового для Украины вида миксомицетов, массовое развитие которого на газонах в г. Донецке вызвало неизвестное ранее явление "обугливания газонов". Даны сведения о его морфологии и распространении. Physarum nudum T. Macbr. is reported as a new species of slime molds for the territory of Ukraine. Its intensive development on lawns in Donetsk city caused the earlier unknown phenomenon of "lawns' charring". Information on Ph. nudum morphology and distribution is provided.